PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA ON-GRID 900 VA DAYA MIKRO APLIKASI RESIDENTIAL MENGGUNAKAN HOMER - Bandri, Sepannur; Anthony, Zuriman; Andari, Rafika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
potential of solar energy sources in Indonesia reaches an average of 4.5 kWh per square meter. PLTS On-Grid PLTS configuration system that is connected to the network with the KWh EXIM tool which functions to send exces electricity by PLTS to the network. There are many conditions for installing PLTS on the roof of a house such as the location of the area, the direction of the roof of the house, the roof area where the solar module will be installed. In this study, 6 units of 330 Wp polycrystalline solar modules were used to meet the needs of the house's electrical load. This PLTS is designed to supply electricity with an estimated daily energy load of around 6.69 kWh. For the planning of this On-grid PLTS, 6. The components needed in this plan are 1 SCC unit, and 1 inverter unit with a PLTS output power of 2,416.227 kWh/year. Performance ratio (PR) in the PLTS system as a reference for the initial investment of Rp. 19,069,000 which covers costs for the components of the PLTS system and operational maintenance costs of Rp. 1906,900Keyword: PLTS, On-grid, Solar Panel, Energy, Solar modul